Chemoenzymatic synthesis of fucosylated oligosaccharides using Thermosynechococcus α1–2-fucosyltransferase and their application in the regulation of intestinal microbiota - Ruting Zhong (Elsevier, 2021)
A novel bacterial α 1–2-fucosyltransferase (α 2FT) from Thermosynechococcus sp. NK55a (Ts2FT) has been discovered and characterized. It shares 28–62% protein sequence homology to α 2FTs reported previously. The Ts2FT was cloned as an N-terminal His6-tagged recombinant protein (His6-Ts2FT) and expressed in E. coli BL21 (DE3). It was expressed at a level of 6.2 mg/L culture after induction with 0.05 mM of isopropylβ-d-1-thiogalactoside (IPTG) at 16 °C for 20 h. It showed the optimal activity at a reaction temperature of 40 °C and pH of 7.0. The presence of a Mg2+ improved its catalytic efficiency. Ts2FT displayed a strict acceptor specificity and could recognize only β1–3-galatoside acceptors. It was used efficiently for one-pot multienzyme synthesis of fucosylated oligosaccharides. One of the products, lacto-N-fucopentaose I was shown to promote the growth of intestinal probiotics including those belonging to Acidobacteria, Actinobacteria, Proteobacteria, Planctomycetes, and Chloroflexi.